2015
DOI: 10.1111/exsy.12120
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive fuzzy handover triggering approach for Long‐Term Evolution network

Abstract: To cope with the increasing demand for efficient data delivery, self‐organizing networks have been introduced in the Long Term Evolution (LTE) system to provide autonomous and flexible mobility management. The existing handover triggering scheme for LTE is not flexible enough to incorporate new performance metrics, and it introduces handover latency. There are studies on non‐conventional handoff algorithms for LTE applications, for instance, the fuzzy logic approach. However, the fuzzy logic approach needs reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Compared with conventional fuzzy logic-based handover triggering mechanisms and other traditional approaches, the proposed algorithm in Reference [20] demonstrated that it provided a significant improvement in handover performance in terms of mobility robustness and mobility load balancing.…”
Section: Intelligent Handover Triggering Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional fuzzy logic-based handover triggering mechanisms and other traditional approaches, the proposed algorithm in Reference [20] demonstrated that it provided a significant improvement in handover performance in terms of mobility robustness and mobility load balancing.…”
Section: Intelligent Handover Triggering Mechanismsmentioning
confidence: 99%
“…However, the approach in Reference [20] was unable to process too many metrics as input parameters; otherwise, the whole system becomes complicated and the training process is time-consuming. In Reference [21], the authors adopted model-free asynchronous advantage actor-critic (A3C) reinforcement learning techniques to learn an optimal handover method.…”
Section: Intelligent Handover Triggering Mechanismsmentioning
confidence: 99%
“…The fuzzy logic is used to initial HO and utility functions are then applied to select the optimal access networks. Paper [9] [10] integrates artificial neuro networks into the fuzzy logic system. In this way, the fuzzy membership functions can dynamically self-adjust based on the changes of environment, which could also improve the system efficiency by reducing human intervention.…”
Section: Related Workmentioning
confidence: 99%
“…Afterwards, the normalised fuzzy decision matrix DM will multiply the fuzzy weight array W to obtain weighted normalised fuzzy decision matrix ̃ as, (9) Based on this normalised fuzzy decision matrix, the fuzzy positive ideal solution ( * ) and fuzzy negative ideal solution ( − ) are calculated by (10) (11),…”
Section: System Modelmentioning
confidence: 99%
“…Reference [13] shows the adaptive handover triggering mechanisms by combining fuzzy logic with neuro networks. In this approach, the subtractive clustering is used to initialise membership functions, which is tuned by using artificial neuro network corresponds to the changes in the mobile environment.…”
Section: Introductionmentioning
confidence: 99%